The Effects of Water to Solid Ratio, Activator to Binder Ratio, and Lime Proportion on the Compressive Strength of Ambient-Cured Geopolymer Concrete - Andi Arham Adam (Journal of the Civil Engineering Forum, 2019)
Low calcium fly ash based Geopolymer has been proven to be one of the potential alternatives substitutes to Portland Cement not only due to its high resistance to chemical attack but also because of the vast availability of class F fly ash for raw materials. However, one of the limitations of geopolymer as the alternative binders in concrete is that the strength develops slowly under ambient condition. This paper presented the investigation of water to solid ratio, activator to binder ratio, and lime proportion on the compressive strength of ambient-cured geopolymer concrete. To develop sufficient strength at an early age, class F fly ash and slaked lime (Ca (OH)2) were used as the binder with the proportion of lime to binder of 4%, 5%, 6%, and 7%. The blended binder was activated by sodium silicate and sodium hydroxide solution with the variation of activator to binder ratio of 0.45, 0.5, 0.55, and 0.6.  The water to solid ratio of 0.30, 0.31, 0.32, and 0.33 was chosen to facilitate good workability which was done by adding water to the mix. The compressive strength tests were conducted at 7, 14, and 28 days on the cylindrical concrete specimens with a dimension of 100 mm diameter and 200 mm height. The results show that the activator to binder ratio of 0.50 to 0.55, and the proportion of lime to the binder of 6% to 7% were the optimum range value. It was also found that the lower the water to cement ratio the higher the compressive strength and the water to solid ratio as low as 0.3 produced the highest compressive strength while still maintaining good workability.